Tingkat Pengetahuan Ibu dalam Penanganan Diare pada Anak Usia 1-5 Tahun - Irma Ayu Malau; Lyna Hutapea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to assess mothers' knowledge level in the pediatric ward of Bandung Adventist Hospital regarding the management of diarrhea in children aged 1 to 5 years. The method used is quantitative descriptive. This study used a questionnaire assessing maternal awareness of childhood diarrhea. Fifty women randomly selected from the Bandung Adventist Hospital pediatric ward became the research sample. The research results showed that 20% of respondents were in the excellent group, while 80% were in the poor category. In conclusion, based on research findings, mothers' knowledge level in treating diarrhea in children aged 1 to 5 years in the children's room at Bandung Adventist Hospital is in the poor category, with 40 respondents. Efforts that can be made to increase mothers' knowledge are by educating parents about preventing and treating diarrhea in toddlers so that it can increase or improve mothers' knowledge. Keywords: Toddlers, Diarrhea, Knowledge